2010
DOI: 10.1007/698_2009_42
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation of Azo Dyes

Abstract: Biodegradation is a cost-effective method to remove the residues of azo dyes prior to their discharge in wastewater streams from dye product industries. The efficacy of this treatment method is highly dependent on establishing an effective degrader community and maintaining environmental conditions that support the growth and activity of the degrader organisms. Although activated sludge is commonly used as a source of degrader organisms to start the process, bioaugmentation of the wastewater with highly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 209 publications
(176 reference statements)
0
14
0
Order By: Relevance
“…Synthetic dyes are complex aromatic compounds used in many industries like paper, printing, textile, food and cosmetics [1]. The major synthetic dyes include azo, triphenylmethane, anthraquinone and metal dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes are complex aromatic compounds used in many industries like paper, printing, textile, food and cosmetics [1]. The major synthetic dyes include azo, triphenylmethane, anthraquinone and metal dyes.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1 , the presence of chitosan into the matrix did not affect significantly the density and the porosity of the structure with respect to the pristine PD [ 27 , 42 ]. Moreover, the water absorption (that is directly correlated to the presence of open pores) and the high value of open porosity suggested that the PDC60 is suitable to be applied as an adsorbent for removing toxic compounds from aqueous media, such as the anionic dye Indigo Carmine [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate products of first step (decolorization process) are degraded by various bacterial enzymes such as hydroxylase and oxygenase (Pandey et al, 2007;Khalid et al, 2009). Furthermore, the selected bacterial strain has the ability to cleave -N=N-bond, probably with the aid of azoreductase enzyme (McMullan et al, 2001;Khalid et al, 2010).…”
Section: Discussionmentioning
confidence: 99%